2021
DOI: 10.22219/agriecobis.v4i2.15922
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences toward Goat Milk

Abstract: The high level of business competition in this current globalization requires companies to produce quality products. Among the efforts of product improvement is through understanding consumer preferences. This study aims to identify consumer preferences of several attribute combinations of goat milk branded Bumiku Hijau, Yogyakarta. Conjoint analysis with pairwise-comparison was employed in this study. The combination of attributes analyzed were price, flavor variant, types of milk, and packaging. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…Parasuraman et al (2021) reported that price of milk has significant association with brand preference in a study of consumers' choice and preferences of dairy based products, in India. Agustina et al (2021) also reported similar results in a study of consumers' preference for goat milk in Indonesia where the price attribute was found to have the highest utilitarian value in terms of preference. Similarly, L. Nguyen (2021) also found price as the strongest predictor of brand choice amongst consumers of Dielac Alpha powdered milk brand in Vietnam.…”
Section: Regression Resultssupporting
confidence: 66%
“…Parasuraman et al (2021) reported that price of milk has significant association with brand preference in a study of consumers' choice and preferences of dairy based products, in India. Agustina et al (2021) also reported similar results in a study of consumers' preference for goat milk in Indonesia where the price attribute was found to have the highest utilitarian value in terms of preference. Similarly, L. Nguyen (2021) also found price as the strongest predictor of brand choice amongst consumers of Dielac Alpha powdered milk brand in Vietnam.…”
Section: Regression Resultssupporting
confidence: 66%
“…Existe evidencia que los factores como el género, la edad y el nivel de educación se vinculan con la preferencia de alimentos que benefician la salud. En la Tabla 2 se observan las características demográficas de los consumidores (encuestados) de la leche de cabra en polvo en la Región de Coquimbo Chile, el 64% son del género femenino, mientras que los consumidores hombres son el 36 %, esto sucede porque las mujeres tienden a tener una naturaleza consuntiva más alta que los hombres, resultados en consecuencia por lo reportado por Nugroho et al (2020) y Agustina et al (2021), las amas de casa, juegan un papel fundamental en la determinación y decisión de los alimentos consumidos por los miembros de su familia. La mayoría de los encuestados tienen entre 31-40 años con un porcentaje del 46% y La mayoría de los niveles de educación de los encuestados son técnico profesional con un total del 44%.…”
Section: Resultados Y Discusiónunclassified
“…Thus, measures should be put in place to promote dairy goat milk as an alternative to dairy cow milk due to its high nutritive value (Turkmen, 2017;Jerop et al, 2014;Ali et al, 2010). Thus, measures should be put in place to promote dairy goat milk as an alternative to dairy cow milk due to its high nutritive value and potential (Bhattarai, 2014;Agustina et al, 2021).…”
Section: Discussionmentioning
confidence: 99%